Studies on the anti-obesity effects of Celosia cristata flower extract in vitro and in vivo - UPRETY LAXMI PRASAD (The Graduate School, Ajou University, 2024)
Obesity, characterized by the accumulation of excess calories in mature adipocytes in the form of lipids, can trigger aberrant metabolic activity. Effective management of obesity-related abnormalities is crucial to control obesity. However, conventional drugs designed to manage obesity frequently exhibit significant long-term adverse effects. In contrast, natural and herbal supplements have minimal or no long-term adverse health effects. Consequently, herbal medicines and supplements have emerged as promising areas of interest, surpassing conventional pharmaceuticals as obesity management strategies. Here, I explored the anti-obesity effects of a Celosia cristata (CC) total flower- extract in vitro using mouse pre-adipocytes 3T3-L1 and adipose-derived stem cells induced by adipogenic differentiation medium and co-treated with varying concentrations of CC (10, 20, and 50 µg/mL). CC shows significant reduction in adipocyte differentiation and lipid droplet accumulation, with diminished intracellular triacylglycerol and increased glycerol concentration in cell supernatant, in a dose-dependent manner. Further, supplementation with CC (25, 50, and 100 mg/kg/day) or Garcinia cambogia (GC, 100 mg/kg/day) as a positive control for varying treatment durations according to diet patterns shows significant body weight reduction, improvements in metabolic abnormalities, enhanced lipolysis-related factors (Hsl, Acox1, and Cpt2), and reduced adipogenesis-related factors (Pparγ, Cebpa, Fabp4, and Fasn) in high-fat diet (HFD)-induced obese mice. In addition, metabolic parameters observed using the metabolic cage monitoring system, demonstrated that CC supplementation increased oxygen consumption (VO2), carbon dioxide expiration (VCO2), respiratory exchange ratio (RER=VCO2/VO2), and energy expenditure (EE) in HFD-induced obese male mice. This leads to decreased body fat and increased lean body mass in mice, complemented by enhanced mRNA expression levels of mitochondrial activities and energy metabolism associated factors (Ucp1, Pgc1a, Prdm16, Cytc, Cox4b, and Mccad) in the epididymal adipose tissue. As a result, these changes inhibited metabolic abnormalities such as hepatic steatosis and adipocyte hypertrophy, as determined by histomorphological analysis of the liver and epididymal adipose tissues. Furthermore, blood plasma biochemical analysis showed that, CC treatment ameliorated the levels of low-density lipoprotein, total cholesterol, triglyceride, and high-density lipoprotein, in HFD-induced obese mice, indicating an improvement in cholesterol-associated abnormalities that usually persist in HFD-fed obese mice, suggesting that CC could be a beneficial natural supplement to mitigate the risk of developing cholesterol-associated diseases. In addition, CC significantly reduced the blood plasma levels of the liver inflammation- related markers; AST and ALT, which highlighted its role in minimizing liver inflammation caused by fat accumulation during HFD-induced obesity. Moreover, CC remarkably improved glucose absorption, and insulin sensitivity in HFD-induced obese mice, as indicated by the outcomes of the oral glucose (OGTT) and insulin tolerance tests (ITT), respectively. In summary, my in vitro and in vivo studies demonstrate that supplementation with CC total flower extract effectively regulates adipogenesis, lipolysis, and mitochondrial energy metabolism-related factors, thereby inhibiting body weight gain and improving obesity-associated abnormalities. These findings suggest that the CC flower extract could be a potential natural herbal supplement for preventing and managing obesity and its associated metabolic disorders. __________________________________________________________________ Keywords: Obesity, Celosia cristata flower, Extract, Adipocytes, High-fat diet, Animal study, Metabolic disorder, Adipogenesis, Lipolysis, Energy metabolism|비만(Obesity)은 에너지의 섭취와 소비의 불균형으로 인해 몸에 비정상적이고 과도하게 지방이 축적된 것을 말한다. 세계보건기구(World Health Organization, WHO)는 ‘건강을 해칠 정도로 지방조직에 비정상적인 또는 과도한 지방이 축적된 상태’로 정의하고 있다. 비만은 비정상적인 대사 활동을 유발하여 제2형 당뇨병, 심혈관질환, 지방간, 고혈혈압, 염증, 암 등의 여러가지 성인병의 중요한 원인이 되는 것으로 밝혀졌다. 최근 전세계적으로 비만 환자가 급증하고 있으며, 개인의 건강 증진과 국가의 의료비 절감을 위해 반드시 해결해야할 문제가 되어있다. 고도 비만의 치료를 목적으로 하는 몇 가지 약물이 개발되어 사용되고 있으나 크고 작은 부작용의 문제가 발생되고 있다. 이에 장기적인 사용에도 부작용이 적은 천연물 유래의 비만 예방, 개선, 치료 물질 개발에 대한 많은 연구가 진행되고 있다._x000D_ 본 연구에서는 다양한 천연물 추출물의 지방세포 분화억제 효능에 대한 탐색(Screening)을 통해 발굴된 맨드라미(Celosia cristata, CC)의 꽃 추출물의 항비만 효과를 조사하고자 하였다. 항비만에 대한 대표적인 시험관 내(In vitro)와 생체 내(In vivo) 실험 시스템을 이용하여 맨드라미(Celosia cristata)의 꽃의 30% 에탄올 추출물(Ethanol extract)의 유효성 평가와 작용기전 규명에 대한 연구를 목표로 하였다. _x000D_ 먼저, 지방전구세포(Preadipocyte)인 3T3-L1 세포와 쥐의 지방유래 줄기세포(Adipose derived stem cell; ADSC)를 사용하여 실험하였다. 지방세포로 분화를 유도한 후, 맨드라미 꽃 추출물을 농도 별(10, 20, 50 µg/ml)로 처리한 결과, 두가지 세포 모두에서 농도 의존적으로 지방세포 분화(Adipocyte differentiation)와 지방세포 내의 지질 방울 축적(Lipid droplet accumulation)이 유의미하게 감소하였다. 또한, 세포 상층액에서 트리아실글리세롤(Triacylglycerol) 농도의 감소와 글리세롤(Glycerol) 농도의 증가가 나타났다. _x000D_ 다음은, 고지방 식이(High-fat diet; HFD)와 정상 식이(Normal diet; ND)로 사육한 수컷 마우스를 사용하여 총 3가지의 독립된 디자인의 동물 실험을 시행하였다(① 마우스에 HFD 식이 시작과 동시에 실험물질 투여 + HFD 식이, ② HFD 식이로 비만 마우스 제작 후 실험물질 투여 + HFD 식이, ③ HFD 식이로 비만 마우스 제작 후 실험물질 투여 + ND 식이). 동물실험 양성 대조군으로는 가르시니아캄보지아 추출물(Garcinia cambogia extract; 100 mg/kg/day)을 사용하였다. 맨드라미 꽃 추출물 농도 별(25, 50, 100 mg/kg/day)로 투여한 결과 상기의 3가지 실험 디자인 모두에서, 대조군과 대비해서 농도 의존적으로 체중 증가 억제, 대사 이상 개선, 지방분해(Lipolysis) 연관 인자(Hsl, Acox1, Cpt2)의 발현 증가, 지방형성(Adipogenesis) 연관 인자(Pparγ, Cebpa, Fabp4, Fasn)의 발현 감소가 나타났다. 또한, 대사 케이지(Metabolic cage) 모니터링 시스템을 통한 대사 관련 인자의 분석 결과, 맨드라미 꽃 추출물 투여 HFD 유도 비만 마우스에서 산소 소비량(Volume of oxygen consumption; VO2), 이산화탄소 생성량(Volume of carbon dioxide production; VCO2), 호흡 교환율(VCO2/VO2, respiratory exchange ratio, RER) 및 에너지 소비(Energy expenditure, EE)의 유의적 증가가 나타났다. 체지방 감소와 근육량 증가와 더불어 부고환 지방 조직(Epididymal adipose tissue)에서의 미토콘드리아 활동 및 에너지 대사 관련 인자(Ucp1, Pgc1a, Prdm16, Cytc, Cox4b, Mccad)의 mRNA 발현량이 증가된 것을 확인하였다. 또한, 마우스 혈장의 생화학 분석 결과, 저밀도 지질 단백질(Low-density lipoprotein; LDL), 총 콜레스테롤(Total cholesterol; TC), 중성지방(Triglyceride; TG)의 유의적인 감소와 고밀도 지질 단백질(High-density lipoprotein; HDL)의 유의적인 증가를 확인하였다. 더욱이, 혈장 내 간 염증 관련 마커인 aspartate transaminase (AST)와 alanine transaminase, aka alanine aminotransferase (ALT)의 수준이 유의미하게 감소되어 있었다. 이러한 결과는 맨드라미 꽃 추출물이 비만 마우스의 지방간 및 지방세포 비대와 같은 대사이상 개선과 중성 지방 및 콜레스테롤 관련 질환의 발병 위험을 줄이는데 큰 효과가 있음을 시사한다. 끝으로, 경구 포도당 내성 검사(Oral glucose tolerance test; OGTT)와 인슐린 내성 검사(Insulin tolerance test; ITT) 결과에서, 포도당 흡수와 인슐린 감수성을 현저하게 개선하였다._x000D_ 결론적으로, 본 연구에서 맨드라미 꽃 추출물은 지방형성 억제, 지방분해 촉진 및 미토콘드리아 에너지 대사 관련 인자 조절을 통하여 HFD에 의한 체중 증가를 억제하고 비만 관련 표현형(Phenotype)을 개선하는 것을 증명하였다. 이러한 연구결과는 맨드라미 꽃 추출물이 향후 비만 및 관련 대사이상 질환의 예방, 개선, 치료에 유용하게 활용될 수 있을 것으로 기대된다._x000D_ _______________________________________________________________________________________________x000D_ 키워드: 비만, 맨드라미 꽃, 추출물, 지방세포, 고지방식이, 동물실험, 대사이상 질환, 지방형성, 지방분해, 에너지 대사
학위논문(박사)--의생명과학과,2024. 8
Keywords: Adipocytes; Adipogenesis; Animal study; Celosia cristata flower; Energy metabolism; Extract; High-fat diet; Lipolysis; Metabolic disorder; Obesity